Histomorphometric, immunohistochemical and microtomographic comparison between autogenous and xenogenous bone blocks for mandibular lateral augmentation in rabbits - Silva, Erick Ricardo; Balan, Vitor Ferreira; Botticelli, Daniele; Soldini, Claudio; Okamoto, Roberta [UNESP]; Xavier, Samuel Porfirio (MDPI, 2021)
Background: The volumetric and biological behaviors of equine block grafts compared with autogenous block grafts have not yet been assessed. Hence, the aim of the present study was to compare—by means of histomorphometry, immunohistochemistry and microtomography—the graft incorporation and remodeling processes of autogenous and equine xenogenous bone blocks used for mandibular lateral augmentation in rabbits. Methods: Autogenous bone grafts harvested from the iliac bony crest and equine block grafts were secured to the lateral aspect of the mandible angle of eighteen rabbits. The healing after 7, 20 and 60 days was assessed in six animals each period. Results: After 60 days, new bone was present 24.2 ± 11.2% and 31.6 ± 13.3% in the autograft and xenograft groups, respectively. A better integration to the recipient sites was observed in the autogenous compared with the xenogenous blocks. Conclusions: Both xenogenous and autogenous bone blocks presented similar percentages of newly formed bone over time. However, bone volume, the quality of the grafted area and graft incorporation to the recipient sites were superior in the autogenous compared with the equine xenogenous graft sites.
Keywords: Histomorphometry; Immunohistochemistry; Microtomography; Rabbit; Xenograft